Bibelske profetier og deres betydning for kristnes syn på det jødiske folk og staten Israel - Andersen, Ole (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
Christians have widely different views concerning the Jewish people and the state of Israel. The interpretation of the Biblical prophecies about the people and the land of Israel is one of the important factors as regards the view of Christians concerning the Jewish people. The prophecies about Israel in the Bible predict that the people of Israel will be sent into exile throughout the world – in the last days, however, they will return to the land of Israel, and there they will experience a renewal of their relationship with God. From the early church, Christian interpretations of the prophecies about Israel can be gathered into two groups. The so-called church interpretation says that Christians should interpret the prophecies to be about the Christian church (supersessionism). According to the so-called Israel interpretation, on the other hand, Christians ought to read the prophecies about the land and people of Israel. A Christian canon understanding is based on the fact that the Hebrew Bible and the New Testament together make one book with one plot. The book begins with a perfect Paradise under the blessing of God (Genesis 1-2). By the fall, the world is cursed (Genesis 3). Therefore, God chooses the people of Israel to be His tool for restoring the blessing (Genesis 12:1-3). The Messiah comes and accepts the curse and punishment for the destruction of the world (Galatians 3:13-14). When the Messiah returns, He will ultimately remove all curses and restore the blessing from Paradise (Revelation 21-22). This biblical story of redemption shows that the people of Israel are still God’s people, because the blessing will first be finally restored by the return of Jesus. Therefore, Christians should interpret the prophecies to be about Israel. If Christians do so, the result will, on the one hand, become sympathy for the Jewish people and the state of Israel and a clear no to ecclesiastical anti-Semitism and, on the other hand, a no, which is equally clear, to demonization and hatred of the Palestinians.